Women as Pillars of Coastal Economic Resilience: Role Transformation, Empowerment, and Gender Support in the Juwana Coastal Community - Arisanti Ayu Wardhani; Sherly Arwinda; Achmad Solechan; Ahmad Hafiyyan Shibghatalloh; Hasan Aminda Syafrudin; Cici Musliha (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the division of gender roles within small-scale fishing households and to identify the empowerment of fishers’ wives that has already taken place in Juwana District. The research focuses on two villages in Juwana District, Pati Regency: Bendar and Bumirejo. The approach used in this study is mixed methods, combining a quantitative approach with descriptive statistics and a qualitative approach using triangulation. Data are collected through in-depth interviews with 60 fisher families using the snowball sampling method. The results show that women in fishing households play a crucial role not only in domestic (reproductive) affairs but also in economic (productive) activities such as fish processing, entrepreneurship, and cooperative management. Furthermore, women are active in social and community activities (managing community). Women’s empowerment is reflected in three main dimensions: resources (access to training, capital, and social support), agency (the ability to make decisions within the family and community), and achievements (increased financial independence and family welfare). The success of empowerment is supported by women’s confidence and skills, family support-especially from husbands-and facilitation from the government and other stakeholders.